Carbonic Anhydrase I and II Inhibition with Natural Products: Leucas cephalotes - Sethi, Kalyan K.; Verma, Saurabh M.; Kumar, P. Mahesh; Mishra, Rahul; Supuran, Claudiu T. (Pharmacognosy Communications)
Carbonic anhydrases (EC 4.2.1.1) are ubiquitous metalloenzymes present in prokaryotes and eukaryotes that are encoded by five evolutionarily unrelated gene families are involved in numerous physiological and pathological processes. Novel interesting chemo types, in addition to the sulphonamide and sulfamate were discovered, many of which are based on natural products, such as phenols/polyphenols, phenolic acids, and coumarins. Methanolic extract of Leucas cephalotes belongs to family Labiatae (or Lamiaceae) tested for human carbonic anhydrase (hCA) I and II inhibition study. The significant IC 50 values are calculated for the methanolic extract of Leucas cephalotes for hCA I found to be 0.23 mM/ml which is showing relatively less potent then hCA inhibition against hCA II having IC 50 values of 0.19 mM/ml. Leucas cephalotes is a weak inhibitors they may constitute leads for developing tighter binding compounds.
Keywords: Carbonic anhydrase; Enzyme inhibitor; Natural product; Leucas cephalotes